The Satisfaction Level of Undergraduate Engineering Students on Distance Learning Amidst COVID-19 - Jereco Jims Agapito; Genaro Japos (JPAIR, 2021)
Distance learning is the primary solution of the educational system in the entire world. Online mode also led the undergraduate engineering students. This study was a prospective, cross-sectional, and observational study. There were 20 questions, each of which was scored using the Likert scale. The data collection was done on an electronic platform. The data are presented in frequencies and percentages using Jamovi to analyze the data and the outcomes of the hypotheses. A total of 170 engineering students participated in the study and 2 of them disagreed with consent and were excluded. A total of 64 (37.76%) participants gave students positive responses (Very satisfied and Satisfied). A total of 71 (42%) participants gave a negative response to online learning (Very dissatisfied and Dissatisfied). A t-test provided evidence of no statistically significant difference in the student’s satisfaction regarding distance learning between male and female students. ANOVA test shows no statistically significant difference in the student’s satisfaction relating to distance learning between BSCE, BSEE, and BSME. Large engineering students were dissatisfied with the online mode of teaching due to various reasons. They are generally satisfied with the support and response from the teaching faculties and dissatisfied with the communication/technology issues and lack of practical or clinical learning.